The output composition puzzle: a difference in the monetary transmission mechanism in the euro area and U.S. - Benoît Mojon; Ignazio Angeloni; Daniele Terlizzese; Anil K. Kashyap (European Central Bank (ECB), 2003)
We revisit recent evidence on how monetary policy affects output and prices in the U.S. and in the euro area. The response patterns to a shift in monetary policy are similar in most respects, but differ noticeably as to the composition of output changes. In the euro area investment is the predominant driver of output changes, while in the U.S. consumption shifts are significantly more important. We dub this difference the output composition puzzle and explore its implications and several potential explanations for it. While the evidence seems to point at differences in consumption responses, rather than investment, as the proximate cause for this fact, the source of the consumption difference remains a puzzle.
Keywords: E21; E22; E30; E52; 330; business cycles; Consumption; Investment; Monetary policy transmission